The role of the "how it's made " program to guidance university students to develop industrial and social knowledge - Khutob, Eman Mohammed; Tujjaralshahy, Alia Abdalhakeem (Journal of Educational and Psychological Sciences, 2022)
This study aims to develop industrial and social knowledge among university students, who are non- industrial specialists. By activating the How It's Made program, which is a tool for industrial knowledge as extracurricular activities based on constructive thinking in educational program design and knowledge theory. The problem of the research is determined that industrial and social knowledge did not receive a share of the programs that are interested in simplifying it, such as the one that came in the How It's Made program, as it did not receive enough attention in the field of research and scientific studies. The research has adopted the experimental descriptive approach. The two research tools were built to help identify and solve the problem, which is design closed and open questionnaire and pre and post questionnaire as well as to design extracurricular activities which is how it's made and activated to the sample. Then statistically analyze the data using SPSS. The study found: The most approved sentences from the sample members were their expectations for the impact of the How It's Made program in the production of a science-educated generation (92.2%). The current research is thus the first study to demonstrate the importance and effectiveness of a program- how it's made for industrial and social aspects.
Keywords: role; how it's made; Industrial knowledge development; development